A lithium manganese phosphate precursor, a cathode material and a preparation method of the cathode material

By gradient co-doping of cobalt and aluminum ions in the lithium manganese phosphate precursor and combining it with a highly conductive carbon network, the problems of insufficient conductivity and diffusion capacity of lithium manganese phosphate cathode materials were solved, thereby improving battery capacity and cycle performance.

CN119306593BActive Publication Date: 2026-11-06浙江格派钴业新材料有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411414583.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2026-11-06
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The electronic conductivity and lithium-ion diffusion capacity of existing lithium manganese phosphate cathode materials are limited, which restricts the improvement of battery energy density.

Method used

A gradient co-doping method was used to dope cobalt and aluminum ions into the lithium manganese phosphate precursor, gradually changing the concentration from the inside to the outside of the particle, and combining it with a highly conductive carbon network. The lithium manganese phosphate cathode material was prepared by controlling the synthesis process.

Benefits of technology

It improves the diffusion rate of lithium ions, enhances structural stability, and improves the conductivity of electrons and ions, thereby increasing the battery capacity and cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306593B_ABST
    Figure CN119306593B_ABST
Patent Text Reader

Abstract

The present application relates to the field of lithium ion battery, and particularly relates to a lithium manganese phosphate precursor, a positive electrode material and a preparation method of the positive electrode material. The present application dopes Co ions in the manganese oxalate precursor, so that Co ions are doped in the finally synthesized lithium manganese phosphate, and the content gradually decreases from inside to outside along the lithium manganese phosphate particles. The Co element doping can reduce the migration barrier, improve the diffusion rate of lithium ions, and thus improve the conductivity performance, and is also beneficial to the capacity of the material. Similarly, the present application adopts Al element doping, and the content gradually increases from inside to outside along the lithium manganese phosphate particles. This is because Al as an inert element is doped in the outer layer, which can significantly alleviate the irreversible phase change, thereby inhibiting the generation of micro-cracks, enhancing the structural stability, and thus improving the cycle capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion batteries, specifically to a lithium manganese phosphate precursor, a cathode material, and a method for preparing the cathode material. Background Technology

[0002] In recent years, with the iterative upgrading of technology, the continuous improvement of the energy density of lithium iron phosphate batteries and the large-scale application of module-free CTP, the battery life of lithium iron phosphate batteries has been greatly improved, making up for the shortcoming of low battery life. With its low cost, excellent safety performance and long cycle life, lithium iron phosphate batteries have rapidly increased their market share and become the mainstream in the market.

[0003] The cathode material of lithium-ion batteries is a key factor affecting battery performance. The commercially available lithium iron phosphate (LFP) cathode material has a relatively low operating voltage, which cannot meet the demands of high-energy-density lithium-ion batteries. Like LFP batteries, lithium manganese phosphate (LMP) is also a olivine-type phosphate-based lithium battery cathode material. This material has higher safety and cycle life than traditional layered cathode materials such as lithium cobalt oxide and ternary materials. However, the 3.4V potential of the widely used LFP limits the improvement of battery energy density, while LFP has a higher potential of 4.1V. Therefore, under the same capacity conditions, LFP batteries can achieve an energy density approximately 20% higher than LFP batteries. Olivine-type LFP is currently a research hotspot for cathode materials, possessing advantages such as low cost, low toxicity, good cycle performance, structural stability, and high energy intensity. However, similar to LFP, LFP's electronic conductivity and lithium-ion diffusion capacity are severely limited by its structure.

[0004] Therefore, improving the electrochemical performance of lithium manganese phosphate and refining its synthesis methods are key research areas in this field. Summary of the Invention

[0005] The purpose of this invention is to provide a gradient co-doped manganese oxalate precursor, and to prepare an excellent lithium manganese phosphate cathode material using this material. The specific solution is as follows:

[0006] A lithium manganese phosphate precursor, wherein the general chemical formula of the lithium manganese phosphate precursor is Mn 1-x-y Co x Al y C2O4·2H2O, 0.01≤x≤0.05, 0.01≤y≤0.05; The lithium manganese phosphate precursor is doped with cobalt ions and aluminum ions. Along the manganese oxalate particles, the content of cobalt ions gradually decreases from the inside to the outside, while the content of aluminum ions gradually increases.

[0007] The general chemical formula of the lithium manganese phosphate cathode material is Mn. 1-x-y Co x Aly PO4 / C, 0.01≤x≤0.05, 0.01≤y≤0.05; The lithium manganese phosphate cathode material is doped with cobalt ions and aluminum ions. Along the lithium manganese phosphate particles, the content of cobalt ions gradually decreases from the inside to the outside, while the content of aluminum ions gradually increases.

[0008] The total mass of lithium manganese phosphate and carbon is 100 wt%, and the carbon content is 3% to 9%.

[0009] A method for preparing lithium manganese phosphate cathode material, comprising the following steps:

[0010] (1) Prepare Mn source, Al source, Co source and oxalic acid solution;

[0011] (2) Mn source and oxalic acid solution are added to a reaction vessel filled with inert gas at a fixed flow rate. At the same time, the flow rate of Co source solution is gradually reduced and the flow rate of Al source solution is gradually increased to carry out a co-precipitation reaction and obtain a mixed slurry.

[0012] (3) Separate the slurry to obtain filter cake, and then dry it;

[0013] (4) The dry precursor is dry-mixed with carbon source, lithium source and phosphorus source, and calcined to obtain Al and Co gradient co-doped lithium manganese phosphate cathode material.

[0014] The Mn source is selected from one or more of manganese nitrate, manganese sulfate, and manganese chloride, and the concentration of the manganese source solution is 1 to 3.0 mol / L; the molar ratio of oxalic acid solution to Mn source solution is 1 to 1.2:1.

[0015] The total amount of Mn source or oxalic acid solution is S1, and the injection rate into the reactor is V1. The total amount of Co source or Al source solution is S2. Then, the Co source solution is injected at an initial flow rate of V2. The amplitude decreased linearly, and the Al source solution was injected at an initial flow rate of 0. The amplitude increases linearly, 10mL / min≤V1≤50mL / min, 1.8L≤S1≤9L, 0.3L≤S2≤0.9L.

[0016] In step (4), the carbon source includes a combination of organic carbon source and inorganic carbon source. The inorganic carbon source includes one or more carbon materials in the form of graphene, carbon nanotubes, acetylene black, graphite, carbon black, etc. The organic carbon source includes one or more of glucose, sucrose, starch, citric acid, polyethylene glycol, phenolic resin, polydopamine.

[0017] In step (4), the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate, lithium oxalate, and lithium dihydrogen phosphate, and the phosphorus source includes one or more of phosphoric acid, ammonium dihydrogen phosphate, ammonium phosphate, ammonium monohydrogen phosphate, and lithium dihydrogen phosphate.

[0018] In step (4), the dry-mixed powder is placed in a tube furnace and calcined in a two-step process under a high-purity nitrogen atmosphere.

[0019] The specific steps of the two-step calcination are as follows: Pre-calcination: heat from room temperature to 350-500℃ at 5℃ / min, hold for 4-8 hours, and cool to room temperature before taking out; Grinding: grind in a mortar with anhydrous ethanol until the powder is uniform, and then dry; Re-calcination: heat from room temperature to 600-700℃ at 5℃ / min, hold for 7-10 hours, and then cool to obtain the sample.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The present invention dops Co ions in the manganese oxalate precursor, thereby making the final synthesized lithium manganese phosphate doped with Co ions, and the content gradually decreases from the inside to the outside along the lithium manganese phosphate particles. Co element doping can reduce the migration barrier, increase the diffusion rate of lithium ions, thereby improving its conductivity and also benefiting the material capacity.

[0022] (2) Similarly, the present invention uses Al element doping, and the content gradually increases from the inside to the outside along the lithium manganese phosphate particles. This is because Al, as an inert element, is incorporated into the outer layer, which can significantly alleviate irreversible phase transition, thereby suppressing the generation of microcracks, enhancing structural stability, and thus improving cycle capability.

[0023] (3) By controlling and adjusting the preparation method during the precursor synthesis process, the present invention synthesizes gradient-doped Al and Co in the precursor, thereby ensuring that gradient doping elements also exist in the lithium manganese phosphate cathode. Furthermore, through the synergistic effect of the highly conductive carbon network, the lithium manganese phosphate cathode material can achieve efficient electron and ion conduction, thereby improving the battery capacity and cycle performance. Attached Figure Description

[0024] Figure 1 XRD pattern of the gradient co-doped manganese oxalate precursor prepared in Example 1;

[0025] Figure 2 The XRD pattern of the gradient co-doped lithium manganese phosphate cathode material prepared in Example 1;

[0026] Figure 3 SEM image of the gradient co-doped manganese oxalate precursor prepared in Example 1. Detailed Implementation

[0027] The technical solutions of the present invention will now be described in detail with reference to the accompanying drawings.

[0028] Example 1

[0029] According to LiMn 0.94 Co 0.03 Al 0.03 Prepare 6 L of 2 mol / L MnSO4 solution, 6 L of 2.1 mol / L oxalic acid solution, 0.6 L of 0.638 mol / L CoSO4 solution, and 0.6 L of 0.638 mol / L Al(NO3)3 solution using the stoichiometric ratio of PO4.

[0030] The reaction vessel was filled with inert nitrogen gas. MnSO4 solution and oxalic acid solution were injected into the reaction vessel in a co-current flow at a rate of 20 mL / min. Simultaneously, Co source solution was injected at an initial flow rate of 4 mL / min, followed by a final flow rate of 0.013 mL / min. 2 The amplitude decreased linearly, and the Al source solution was injected at an initial flow rate of 0, followed by a flow rate of 0.013 mL / min. 2 The amplitude increases linearly, and a co-precipitation reaction occurs to obtain a mixed slurry;

[0031] After the coprecipitation reaction, the mixture is centrifuged, washed, and filtered multiple times to obtain a filter cake, which is then dried using a dryer.

[0032] Weigh 1 mol of Mn 0.94 Co 0.03 Al 0.03 C2O4·2H2O, 1 mol LiH2PO4, 3.14 g graphene, and 20.41 g glucose were dry-mixed for 1 hour. The dry-mixed powder was then placed in a tube furnace and sintered in two steps under a high-purity nitrogen atmosphere.

[0033] Preheating: Increase the temperature from room temperature to 450℃ at a rate of 5℃ / min, hold for 5 hours, and then cool to room temperature before removing.

[0034] Grinding: Grind in a mortar with anhydrous ethanol until the powder is uniform, then dry;

[0035] Reheating: The temperature was increased from room temperature to 680℃ at a rate of 5℃ / min, held for 8 hours, and then cooled to obtain the sample.

[0036] Example 2

[0037] The difference from Example 1 is that, according to LiMn 0.94 Co 0.04 Al 0.02 The ingredients are prepared according to the stoichiometric ratio of PO4.

[0038] Example 3

[0039] The difference from Example 1 is that, according to LiMn 0.94 Co 0.02 Al 0.04 The ingredients are prepared according to the stoichiometric ratio of PO4.

[0040] Example 4

[0041] The difference from Example 1 is that CNTs are replaced with graphene.

[0042] Comparative Example 1

[0043] The difference from Example 1 is that it is not doped with Co ions and Al ions.

[0044] Comparative Example 2

[0045] The difference from Example 1 is that Co ions and Al ions are injected into the reactor at a constant flow rate of 2 mL / min.

[0046] Comparative Example 3

[0047] The difference from Example 1 is that highly conductive CNTs are not added.

[0048] Weigh the prepared active material, acetylene black, and PVDF according to a mass ratio of 8:1:1, mix them evenly in a mortar, add an appropriate amount of NMP and continue grinding until a uniform slurry is obtained. Lay the aluminum foil flat on a clean glass plate, and use a four-sided wet film preparation device (coating thickness specification selected is 250μm) to coat the slurry onto the aluminum foil to form an electrode sheet of uniform thickness. Place it in a vacuum drying oven and dry it at 120℃ for 6 hours. Use a button cell punching machine to prepare the cutting, punch the electrode sheet into 14mm diameter electrode sheets, and assemble them in the order of negative electrode shell, lithium sheet, separator, positive electrode sheet, gasket, spring sheet and positive electrode shell. During the process, add an appropriate amount of electrolyte. Finally, encapsulate the battery on a packaging machine and conduct charge and discharge tests on the battery. The test results are shown in Table 1 below.

[0049] Table 1 Performance Test Results

[0050]

[0051] Figure 1 The XRD pattern of the manganese oxalate precursor prepared in Example 1 matches well with the standard card in PDF#23-0293, and no obvious impurity peaks were found. Observation of the diffraction peak intensity indicates that the synthesized material has high crystallinity. Figure 2The XRD pattern of the sample prepared in Example 1 is shown. By comparing it with the card in PDF#98-016-7253, it can be seen that the prepared sample has an olivine structure and belongs to the Pnmb space group. The main crystal plane diffraction peaks of the sample, such as (011), (021), (200), (031), and (131), correspond well with the standard pattern. The diffraction peaks are sharp and there are no impurity peaks, indicating that the prepared sample has good crystallinity.

[0052] Figure 3 The manganese oxalate precursor prepared in Example 1 was tested by SEM, and the results are shown in the figure. The material synthesized by the co-precipitation method exhibits a polyhedral columnar structure with a length of about 10 μm and is uniformly dispersed.

[0053] As shown in Table 1, the electrical performance of Examples 1-4 is significantly improved compared to Comparative Examples 1-3. This is because the gradient co-doping of Co and Al ions in this application can simultaneously improve the conductivity and cycle stability of the cathode active material. Furthermore, due to the synergistic effect of the two metal ions, combined with the construction of highly conductive CNT or graphene networks, efficient electron and ion conduction can be achieved when preparing lithium manganese phosphate cathode materials, thereby improving battery capacity and cycle performance.

[0054] The technical solution of the present invention has been described above with reference to the preferred embodiments shown in the accompanying drawings. However, it will be readily understood by those skilled in the art that the scope of protection of the present invention is obviously not limited to these specific embodiments. Without departing from the principles of the present invention, those skilled in the art can make equivalent substitutions or replacements to the relevant technical features, and the technical solutions after these modifications or substitutions will all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a lithium manganese phosphate cathode material, characterized in that, The steps are as follows: (1) Prepare Mn source, Al source, Co source and oxalic acid solution; (2) Mn source and oxalic acid solution are added to a reaction vessel filled with inert gas at a fixed flow rate. At the same time, the flow rate of Co source solution is gradually reduced and the flow rate of Al source solution is gradually increased to carry out a co-precipitation reaction and obtain a mixed slurry. (3) Separate the slurry to obtain filter cake, dry it to obtain lithium manganese phosphate precursor; (4) The dry lithium manganese phosphate precursor is dry mixed with carbon source, lithium source and phosphorus source, and calcined to obtain Al and Co gradient co-doped lithium manganese phosphate cathode material. The manganese source is selected from one or more of manganese nitrate, manganese sulfate, and manganese chloride, and the concentration of the manganese source solution is 1~3.0 mol / L; the molar ratio of oxalic acid solution to manganese source solution is 1~1.2:1; If the total amount of Mn source or oxalic acid solution is S1, and the injection rate into the reactor is V1, and the total amount of Co source or Al source solution is S2, then the Co source solution is injected at an initial flow rate of V2. ,by The amplitude decreased linearly, and the Al source solution was injected at an initial flow rate of 0. The amplitude increases linearly, 10 mL / min ≤ V1 ≤ 50 mL / min, 1.8 L ≤ S1 ≤ 9 L, 0.3 L ≤ S2 ≤ 0.9 L; The general chemical formula of the lithium manganese phosphate precursor is Mn. 1-x-y Co x Al y C2O4·2H2O, 0.01≤x≤0.05, 0.01≤y≤0.05; the lithium manganese phosphate precursor is doped with cobalt ions and aluminum ions, and along the manganese oxalate particles from the inside to the outside, the content of cobalt ions gradually decreases and the content of aluminum ions gradually increases. The lithium manganese phosphate cathode material has the general chemical formula LiMn. 1-x-y Co x Al y PO4 / C, 0.01≤x≤0.05, 0.01≤y≤0.05; The lithium manganese phosphate cathode material is doped with cobalt ions and aluminum ions. Along the lithium manganese phosphate particles, from the inside to the outside, the content of cobalt ions gradually decreases and the content of aluminum ions gradually increases. The carbon content is 3% to 9% based on a total mass of lithium manganese phosphate and carbon of 100 wt%.

2. The method for preparing a lithium manganese phosphate cathode material as described in claim 1, characterized in that: In step (4), the carbon source includes a combination of organic carbon source and inorganic carbon source. The inorganic carbon source is selected from one or more carbon materials in the form of graphene, carbon nanotubes, acetylene black, graphite, carbon black, etc., and the organic carbon source is selected from one or more glucose, sucrose, starch, etc.

3. The method for preparing a lithium manganese phosphate cathode material as described in claim 1, characterized in that: In step (4), the lithium source is selected from one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate, lithium oxalate, and lithium dihydrogen phosphate, and the phosphorus source is selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, ammonium phosphate, monoammonium phosphate, and lithium dihydrogen phosphate.

4. The method for preparing a lithium manganese phosphate cathode material as described in claim 1, characterized in that: In step (4), the dry-mixed powder is placed in a tube furnace and calcined in a two-step atmosphere of high-purity nitrogen.

5. The method for preparing a lithium manganese phosphate cathode material as described in claim 4, characterized in that: The specific steps of the two-step calcination are as follows: Pre-calcination: heat from room temperature to 350-500 ℃ at a rate of 5 ℃ / min, hold for 4-8 hours, and cool to room temperature before taking out; Grinding: Grind in a mortar with anhydrous ethanol until the powder is uniform and dry; Re-firing: Heat from room temperature to 600-700℃ at 5℃ / min, hold for 7-10 hours, and then cool to obtain the sample.

Citation Information

Patent Citations

  • Lithium manganese phosphate positive pole material and preparation method thereof

    CN102694168A

  • Gradient-doped manganese iron oxalate precursor and preparation method thereof

    CN104710302A

  • Doped lithium iron manganese phosphate positive electrode material, preparation method thereof, positive electrode plate containing doped lithium iron manganese phosphate positive electrode material, and lithium ion battery containing doped lithium iron manganese phosphate positive electrode material

    CN116741987A